The role of mental models in strategic decisions: comparative field research on a sample of Iraqi government and private insurance companies in Baghdad - Mahdi Ali *, Ahmed; A. Al-Kubaisy, Salah Al-Din. (Journal of Economics and Administrative Sciences, 2024)
This research seeks to measure the role of mental models in their dimensions (equipment, implementation, interaction, compatibility, timing) in the strategic decision in its dimensions (identification, development, selection). The field of research consisted of three government insurance companies and seven private insurance companies in Baghdad. Obtaining the necessary data for the field aspect through questionnaires, personal interviews, and company documents, and the researcher adopted the descriptive analytical approach and the comparative approach, as a purposive sample was drawn of (63) individuals with the rank of assistant director and head of department in government companies from a population size of (71), while the number of The number of sample members for private insurance companies was (53) out of a population size of (69). A set of statistical methods were used to process the data, including (normal distribution test, exploratory factor analysis, Cronbach’s alpha test, questionnaire reliability using the split-half method, percentage, arithmetic mean, The standard deviation, the coefficient of variation, the multiple regression coefficient, the interpretation coefficient R2, as well as the Pearson correlation coefficient. The data were analyzed using statistical programs (SPSS V.26, AMOS V.23), and the most prominent findings of the research were the existence of a correlation A significant impact of mental models and their dimensions and the strategic decision with its dimensions. Research type: Research paper